Utility of immunodeficient mouse models for characterizing the preclinical pharmacokinetics of immunogenic antibody therapeutics. Issue 8 (16th November 2016) - Myzithras, Maria; Bigwarfe, Tammy; Li, Hua; Waltz, Erica; Ahlberg, Jennifer; Giragossian, Craig; Roberts, Simon
ABSTRACT: Prior to clinical studies, the pharmacokinetics (PK) of antibody-based therapeutics are characterized in preclinical species; however, those species can elicit immunogenic responses that can lead to an inaccurate estimation of PK parameters. Immunodeficient (SCID) transgenic hFcRn and C57BL/6 mice were used to characterize the PK of three antibodies that were previously shown to be immunogenic in mice and cynomolgus monkeys. Four mouse strains, Tg32 hFcRn SCID, Tg32 hFcRn, SCID and C57BL/6, were administered adalimumab (Humira®), mAbX and mAbX-YTE at 1 mg/kg, and in SCID strains there was no incidence of immunogenicity. In non-SCID strains, drug-clearing ADAs appeared after 4–7 days, which affected the ability to accurately calculate PK parameters. Single species allometric scaling of PK data for Humira® in SCID and hFcRn SCID mice resulted in improved human PK predictions compared to C57BL/6 mice. Thus, the SCID mouse model was demonstrated to be a useful tool for assessing the preclinical PK of immunogenic therapeutics.